2002
DOI: 10.1159/000049146
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of White Matter Lesions

Abstract: Magnetic resonance imaging (MRI) is very sensitive for the detection of white matter lesions (WML), which occur even in normal ageing. Intrinsic WML should be separated from physiological changes in the ageing brain, such as periventricular caps and bands, and from dilated Virchow-Robin spaces. Genuine WML are best seen with T2-weighted sequences such as long TR dual-echo spin-echo or FLAIR (fluid-attenuated inversion recovery); the latter has the advantage of easily separating WML from CSF-like lesions. Abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 21 publications
1
123
0
2
Order By: Relevance
“…Even so, leukoaraiosis was more prominent for VRSs than other factors such as global atrophy, consistent in the present and other studies. 19,29,30 Indeed, the VRSs and leukoaraiosis have similar pathogenesis; both are triggered by the slow occlusion of interstitial fluid due to the deposition of ␤-amyloid in the cortical and leptomeningeal arteries in AD. 24,31 It is known that the prevalence of VRSs increases with advanced age, 3,4 and our data verify this.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, leukoaraiosis was more prominent for VRSs than other factors such as global atrophy, consistent in the present and other studies. 19,29,30 Indeed, the VRSs and leukoaraiosis have similar pathogenesis; both are triggered by the slow occlusion of interstitial fluid due to the deposition of ␤-amyloid in the cortical and leptomeningeal arteries in AD. 24,31 It is known that the prevalence of VRSs increases with advanced age, 3,4 and our data verify this.…”
Section: Discussionmentioning
confidence: 99%
“…12 We believe FLAIR images should be used because they seem to have a higher specificity and accuracy compared with T2 images, especially in the periventricular region. 24,25 As to ICV and BTV, the limits of agreement between automatic and manual were larger compared with inter-/intraobserver limits of agreement.…”
Section: Automatic White Matter Hyperintensity Volumementioning
confidence: 94%
“…Bilateral and symmetric white-matter lesions are other important features against the diagnosis of multiple sclerosis. Although adult forms of leucodystrophies, such as adrenoleucodystrophy, metachromatic leucodystrophy, and Krabbe disease may have a MRI pattern resembling that of MS, whitematter lesions tend to be bilateral and symmetric (Barkhof & Scheltens, 2002). Diffuse and confluent symmetrical T2-weighted hyperintensities in the deep and periventricular white matter with characteristic involvement of the external capsules and temporal poles are considered highly specific for cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) and may distinguish it from MS (Andreadou et al, 2008;Singhal et al, 2005).…”
Section: Conventional Mri Characteristics Suggesting Alternative Diagmentioning
confidence: 99%
“…Furthermore, the presence of multiple microhaemorrhagic foci, which can be seen on gradient-echo images, is another characteristic feature of CADASIL (Dichgans et al, 2002). Another feature pointing against the diagnosis of MS is significant asymmetry of the white-matter abnormalities, which is usually suggestive of ipsilateral carotid disease (Andreadou et al, 2010;Barkhof & Scheltens, 2002 (Lycklama et al, 2003;Agosta and Filippi, 2007), spinal cord abnormalities are not observed in patients with hypoxic-ischemic disease and are rarely reported in other immune-mediated disorders (Bot et al, 2002), and progressive multifocal leucoencephalopathy . Another characteristic pointing against the diagnosis of MS is the complete disappearance of spinal cord lesions in systemic immune-mediated diseases after steroid or immunosuppressive treatment .…”
Section: Conventional Mri Characteristics Suggesting Alternative Diagmentioning
confidence: 99%